Effectivity of Pipper crocatum leaf solution on plaque - Veransa, Biofoma Mohentaeses; Hadidjah, Dede; Rusminah, Nunung (Padjadjaran Journal of Dentistry, 2015)
Chemical plaque control has been proven effective on decreasing the plaque growth. This research was conducted to determine the effectivity of Pipper crocatum leaf solution for controlling dental plaque. The type of this research was a quasi-experimental research using the crossover design and the double blind system. The research sample consisted of 30 female student of Faculty of Dentistry Universitas Padjadjaran, chosen by purposive sampling method. The research subject get treated two times, which were gargled with Pipper crocatum leaf solution or with mineral water three times in two days. Plaque value was assessed using Quiqley and Hein Modified Index by Turesky, Gilmore and Glickman. The plaque scoring was performed on the third day. The data was analyzed by the independent t-test. Results: There was a decrease in the plaque value of the subject that gargled with Pipper crocatum leaf solution, whereas in the subjects gargled with mineral water was found an increasing plaque value. Statistical calculations given the results that there was a significant difference in the plaque value between subjects gargled with Pipper crocatum leaf solution and mineral water. The conclusion of this research was that gargling with Pipper crocatum leaf solution was effective to prevent dental plaque growth.